FORESIGHT AS A TOOL FOR RESPONSIBLE PUBLIC MANAGEMENT AND ADJUSTMENT OF INTERNATIONAL ECONOMIC POLICY IN THE FOCUS OF GLOBAL DEVELOPMENT PROBLEMS - PANCHENKO, Volodymyr; REZNIKOVA, Nataliia; IVASHCHENKO, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The purpose of the article is to study strategic long-term planning tools that allow timely identification of the latest risks, challenges and threats to international economic development that make it difficult to solve global problems that are a consequence of failures in the coordination of international economic policy. It has been determined that strategic forecasting allows politicians to increase the efficiency of government decision-making by identifying opportunities and threats that may arise in the coming years and decades, and also involves the development of possible strategies to counter them by taking into account the characteristics of the identified trends. The phenomenon of the new economy is characterized. The influence of technological development on the asymmetry of international economic development is determined. It has been established that the problems of international economic development in foresight strategizing include geopolitical rivalry, resource confrontation, energy dependence, deglobalization, disintegration processes, trade fragmentation, gaps in value and supply chains, reinstitutionalization of the system of international economic relations, recession, population aging, unemployment. Foresight forecasting tools that are not aimed at predicting a single “correct future” include: analysis of long-term trends and uncertainties; horizon scanning); scenario planning; shaping a normative future; political games; futures wheels; causal multilevel analysis. Research into long-term trends and uncertainties reveals key factors in different possible futures. The comprehensive observation carried out allows us to identify risks for the macroeconomic environment and proactively formulate a pool of measures to minimize the destructive impact of instability on socio-economic development. Improving foresight research as a critical element of strategic forecasting for solving problems of long-term development affects both theoretical aspects (conceptual approach, conceptual apparatus) and applied aspects (technologies and methods of development) of the development and use of this tool. Strategic planning allows you to develop adequate tools to achieve goals and proactively respond to the challenges of modern development, minimizing costs and compensating for the losses that arise for this reason, which lead to the loss of existing competitive advantages. The difference between forecasts and foresights is noted: forecasts are usually associated with uncontrollable events, while foresights most often deal with events and processes that are clearly controllable, therefore they assess the probability of not only one or another outcome of future events, but also the adoption of certain strategic and management decisions. The ability to distinguish normative approaches (what we want) from pragmatic approaches (what we should) is an important component of thinking in terms of alternative futures